HUBUNGAN KEMANDIRIAN BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS DENGAN HASIL BELAJAR IPAS PADA SISWA KELAS IV DI MIS MUHAMMADIYAH 2 SINGKAWANG - Dian Aisya Intani; Rosmaiyadi; Kamaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is intended to understand the relationship between learning independence and critical thinking skills with the learning outcomes of IPAS for grade IV students in MIS Muhammadiyah 2 Singkawang. The research used was quantitative research with the population dual choleration design in this study was a class IV student of MIS Muhammadiyah 2 Singkawang and used a probably sampling technique sample, namely all class IV students totaling 22 students. Data collection techniques used in this study are learning techniques for learning independence and critical thinking skills tests and testing tests of IPAS learning outcomes. Data analysis techniques used are quantitative analysis techniques in the form of learning independence questionnaires, critical thinking skills tests using mean or average, and learning outcomes tests use mean means or averages. The results of the study show that. 1) The level of student learning independence in class IV in MIS Muhammadiyah 2 Singkawang with the results of 83.7 with very high criteria; 2) The level of critical thinking skills of students in class IV in MIS Muhammadiyah 2 Singkawang. This shows the average value of critical thinking skills of 71.36 with a percentage of 71% high category; 3) The level of student learning outcomes in class IV in MIS Muhammadiyah 2 Singkawang. This shows the average value of learning outcomes of 67.7 with a percentage of 67% with a medium category; 4) There is a significant relationship between learning independence and critical thinking skills and IPAS learning outcomes in class IV students of MIS Muhammadiyah 2 Singkawang, namely there is a relationship of 0.513 with sufficient choleration which means there is a significant relationship between the three research variables. It can be concluded that Ho was rejected HA was accepted.